Tyrosinase Inhibition Type of Isolated Compounds Obtained from Pachyrhizus erosus - Endang Lukitaningsih; Muhammad Bahi; Ulrike Holzgrabe (Graduate Program of Syiah Kuala University, 2013)
Abstract - In Indonesia, Bengkoang (Phacyrhizus erosus) have been used as one of cosmetics especially as sun screening and skin whitening materials. Six active compounds in Bengkoang with antioxidant and skin whitening activities have been isolated, namely daidzein, daidzin, genistin, (8,9)-furanyl-pterocarpan-3-ol, 4-(2-(furane-2-yl)ethyl)-2-methyl-2,5-dihydro-furane-3-carbaldehyde and 2-butoxy-2,5-bis(hydroxymethyl)-tetrahydrofurane-3,4-diol. According to literatures, the type of their tyrosinase inhibitory activity has not yet reported. The determination of whitening activity of each compound was evaluated by the evaluation of Lineweaver-Burk plot. The result showed that five compounds had competitive inhibitory activity and 8,9-furanyl-pterocarpan-3-ol showed a non-competitive inhibition. Keywords: Pachyrhizus erosus, tyrosinase, competitive inhibition and non-competitive inhibition